Sonorant Gemination in Old Tamil - Venkatakrishnan, Ramprashanth; Kar, Somdev (Bhasha)
Old Tamil exhibits two kinds of sonorant gemination, which were previously explained by two separate, linear phonological rules. We postulate that the rules explaining both these ‘separate’ phenomena are part of the same conspiracy. This study is devoted to exploring the optimality theoretic analysis of the phenomenon of morphologically derived geminates in Old Tamil, as depicted from Sangam poetic texts and the traditional Tamil Grammars (Tolkāppiyam and Naṉṉūl). We use optimality theoretic markedness or well-formedness constraints like Prosodic Word constraint (ProsWd) and faithfulness constraints like DEP-IO, MAX-IO, NoCoda, etc., as part of the explanatory apparatus. The analysis focuses on a unified ranking of constraints explaining the gemination phenomenon in Old Tamil.